Bang - Timmers, Leo; Timmers, Leo. (Wellington, New Zealand : Gecko Press, 2013)
A line of cars crash into each other causing chaos and humorous animal mix-ups.
Picture story book for children.
Junior.
Keywords: Accidents -- Juvenile fiction; Animals -- Juvenile fiction; Picture books for children; Accidents -- Fiction; Animals -- Fiction; Humorous stories; Accidents; Animals; Picture books for children; Toy and movable books; Children's stories -- Pictorial works; Fiction; Juvenile works; Toy and movable books